2022
DOI: 10.3390/toxins14110806
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Bothrops jararaca Venom Are Diverse in Structure and Protein Composition and Interact with Mammalian Cells

Abstract: Snake venoms are complex cocktails of non-toxic and toxic molecules that work synergistically for the envenoming outcome. Alongside the immediate consequences, chronic manifestations and long-term sequelae can occur. Recently, extracellular vesicles (EVs) were found in snake venom. EVs mediate cellular communication through long distances, delivering proteins and nucleic acids that modulate the recipient cell’s function. However, the biological roles of snake venom EVs, including possible cross-organism commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…Looking beyond venomics, Ogawa et al ( Ogawa et al, 2008 ) provided the first direct isolation and visualisation of EVs from Gloydius blomhoffii snake venom, determining they harbour bioactive cargo that degrades peptides. Expanding on this, Willard et al ( Willard et al, 2021 ) demonstrated quantitative proteomics of venom EVs can identify biomarkers of envenomation, while another study ( Gonçalves-Machado et al, 2022 ) showed venom EVs containing toxin-processing enzymes are internalised by mammalian cells. Together, these pioneering studies indicate venom EVs may facilitate toxin spread and host effects.…”
Section: Evs In Non-mammalian Vertebratesmentioning
confidence: 99%
“…Looking beyond venomics, Ogawa et al ( Ogawa et al, 2008 ) provided the first direct isolation and visualisation of EVs from Gloydius blomhoffii snake venom, determining they harbour bioactive cargo that degrades peptides. Expanding on this, Willard et al ( Willard et al, 2021 ) demonstrated quantitative proteomics of venom EVs can identify biomarkers of envenomation, while another study ( Gonçalves-Machado et al, 2022 ) showed venom EVs containing toxin-processing enzymes are internalised by mammalian cells. Together, these pioneering studies indicate venom EVs may facilitate toxin spread and host effects.…”
Section: Evs In Non-mammalian Vertebratesmentioning
confidence: 99%